Endometriosis and its impact on female infertility (Research, Society and Development, 2022)
This article sought to highlight the relationship between endometriosis and infertility, characterizing aspects of epidemiology, symptoms and diagnosis, focusing on possible causes of infertility in women affected by this pathology. Endometriosis is a chronic inflammatory disease that causes damage to women's health, reproduction, increases the risk of depression, brings limitations in daily life activities and consequent reduction of social and work activity, due to the symptoms that are so characteristic. Infertility caused by endometriosis can be associated with immunological, endocrine or anatomical distortions together with fibrous tissue adhesions. There are currently three therapeutic options available as therapy for endometriosis-associated infertility: clinical treatment, surgery, and technologies adapted for assisted reproduction. Finally, it is clear that endometriosis causes infertility, but requires more research due to the mechanisms by which it leads to this end are not yet fully elucidated and there is no standardized therapy for patients with the pathology.